Factors Associated with Competency of Professional Nurses in Caring Stroke Patients - จงรักษ์, เบญจภรณ์; เลิศสาครศิริ, มาลีวัล; ชินโนรส, สมพร (Princess of Naradhiwas University Journal, 2019)
This descriptive research aimed to study competency of professional nurses who were caring stroke patients. The 169 samples were experienced professional nurses who had been caring stroke patients for one year and over. Research instrument was a questionnaire consisting of personal data, factors relating to the organizational administration, working environment and working motivation, as well as the evaluation form about competency of professional nurses. The questionnaire had been validated by three experts. All of content internal validity index was greater than .05. And the Cronbach’s alpha coefficients were .94, .92, .96 and .93, respectively. Data were analyzed by frequency, percentage, mean, standard deviation and the Pearson’s product moment correlation coefficient. Results from study had shown that the overall mean score of professional nurses’ competency was at a good level (3.87). The highest average score, 4.29, was for nursing care on planning of discharging and the continuity of care, followed by communication and coordination, with an average score of 4.17 (a good level). The lowest average score was 3.17 (a moderate level), for research and nursing development. Organizational administration, working environment, and job motivation had positive correlation with the competency of the professional nurses (r = .40, .26 and .35, p< .01, respectively)